LLT1 and CD161 expression in human germinal centers promotes B cell activation and CXCR4 downregulation - Llibre, A; López-Macías, C; Marafioti, T; Mehta, H; Partridge, A; Kanzig, C; Rivellese, F; Galson, J; Walker, L; Milne, P; Phillips, R; Kelly, D; et al. (American Association of Immunologists, 2016)
Germinal centers (GC) are microanatomical structures critical for the development of high-affinity antibodies and B-cell memory. They are organised into two zones, light and dark, with coordinated roles, controlled by local signalling. The innate Lectin-like transcript 1 (LLT1) is known to be expressed on B-cells, but its functional role in the GC reaction has not been explored. Here we report high expression of LLT1 on GC-associated B-cells, early plasmablasts and GC-derived lymphomas. LLT1 expression was readily induced via BCR, CD40 and CpG stimulation on B-cells. Unexpectedly, we found high expression of the LLT1 ligand, CD161, on Follicular dendritic cells (FDCs). Triggering of LLT1 supported B-cell activation, CD83 upregulation and CXCR4 downregulation. Overall, these data suggest that LLT1-CD161 interactions play a novel and important role in B-cell maturation within the GC in humans.